Relevansi Ontologis dalam Perkembangan Filsafat Ilmu Pengetahuan - Riadi, Dayun; Suradi, Ahmad; Sulistri, Sulistri; Anggita, Lonie; Norvaizi, Ikhrom (Abdurrauf Journal of Education and Islamic Studies, 2025)
This article discusses the development of science that is fundamentally closely related to the role of philosophy, particularly from an ontological perspective. Science functions to elaborate on the phenomena of the universe, while philosophy aims to explain these phenomena with truths obtained through thought based on experience. Therefore, the advancement of science also reinforces the position of philosophy, whose goal is to discover true truths, especially in the context of present-day education. The method of this research is a literature study utilizing secondary data from library sources, documents, and scientific journals. Data was collected through note-taking and literature review related to traditional games. The researcher acted as the main instrument, analyzing the data through reduction, presentation, and simultaneous conclusion drawing to produce conclusions from the literature study. The ontology of science focuses on examining whether a field of knowledge truly exists or not. For instance, in the context of Islamic Educational Management, what is discussed ontologically is not only the existence of its study program but also whether the knowledge taught within it really exists and whether it is different from Educational Management in general. Ontological review is very important in the development of knowledge. By understanding what is considered real and how existence is defined in various disciplines, scholars can build more robust theories philosophically. Ontology is not just an abstract theory, but the foundation that determines the direction and validity of scientific knowledge. Ontological review provides a deep understanding of the metaphysical foundations of knowledge. Abstrak: Artikel ini membahas perkembangan ilmu pengetahuan yang pada dasarnya sangat terkait dengan peran filsafat terkhusus dari tinjauan ontologis. Ilmu pengetahuan berfungsi untuk menguraikan fenomena alam semesta, sementara filsafat bertugas menjelaskan fenomena tersebut dengan kebenaran yang diperoleh melalui pemikiran berdasarkan pengalaman. Oleh karena itu, kemajuan ilmu pengetahuan juga turut memperkuat posisi filsafat, yang tujuannya adalah menemukan kebenaran sejati, terutama dalam konteks pendidikan masa kini.Metode penelitian ini adalah studi pustaka dengan menggunakan data sekunder dari sumber perpustakaan, dokumen, dan jurnal ilmiah. Data dikumpulkan melalui pencatatan dan kajian literatur terkait permainan tradisional. Peneliti berperan sebagai instrumen utama, menganalisis data melalui reduksi, penyajian, dan penarikan kesimpulan secara simultan untuk menghasilkan kesimpulan studi literatur.Ontologi ilmu berfokus pada pemeriksaan apakah suatu ilmu pengetahuan benar-benar ada atau tidak. Misalnya, dalam konteks Manajemen Pendidikan Islam, secara ontologis yang dibahas bukan hanya keberadaan program studinya, tetapi juga apakah ilmu yang diajarkan di dalamnya benar-benar ada dan apakah berbeda dengan Manajemen Pendidikan pada umumnya.Tinjauan ontologis sangat penting dalam pengembangan ilmu pengetahuan. Dengan memahami apa yang dianggap nyata dan bagaimana keberadaan didefinisikan dalam berbagai disiplin ilmu, para ilmuwan dapat membangun teori yang lebih kokoh secara filosofis. Ontologi bukan sekadar teori abstrak, tetapi fondasi yang menentukan arah dan validitas suatu pengetahuan ilmiah. Tinjauan ontologis memberikan pemahaman mendalam tentang fondasi metafisik dari ilmu pengetahuan. Kata kunci: Relevansi, ontologis; filsafat, ilmu pengetahuan